Exendin-4 Protects against Hyperglycemia-Induced Cardiomyocyte Pyroptosis via the AMPK-TXNIP Pathway - Hong Wei; Rui Bu; Qinghui Yang; Jing Jia; Tao Li; Qiuping Wang; Yanjun Chen (Journal of Diabetes Research)
Diabetic cardiomyopathy is a common cardiac condition in patients with diabetes mellitus, which results in cardiac hypertrophy and subsequent heart failure. Chronic inflammation in the diabetic heart results in loss of cardiomyocytes and subsequentially cardiac dysfunction. Accumulated evidence implicated pyroptosis as a vital contributor to the hyperglycemia-induced cardiac inflammatory response. Exendin-4, a GLP analog, promotes survival of cardiomyocytes in cardiovascular diseases, including diabetic cardiomyopathy. However, the role of Exendin-4 in cardiac pyroptosis remains to be elucidated. Our study revealed that Exendin-4 treatment protected against heart remolding and dysfunction and attenuated cardiac inflammation in high-fat diet-fed rats. The activity of caspase-1 and production of pyroptotic cytokines were significantly inhibited by Exendin-4 treatment in the diabetic heart and in high glucose-treated cardiomyocytes as well. In an effort to understand the signaling mechanisms underlying the antipyroptotic property of Exendin-4, we found that blockade of AMPK, an oxidative stress sensor, activity diminished the antipyroptotic property of Exendin-4. Phosphorylation of AMPK resulted in degeneration of TXNIP that promoted the activation of the NLRP3 inflammasome. Exendin-4 treatment decreased the protein level of TXNIP. Moreover, RNA silencing of TXNIP mimicked the antipyroptotic actions of Exendin-4. These findings promoted us to propose a new signaling pathway mediating cardioprotective effect of Exendin-4 under hyperglycemic conditions: Exendin-4 → ROS↓ → pAMPK↑ → TXNIP↓ → caspase-1↓ → IL-1β and IL-18↓ → pyroptosis↓. In general, our study identified Exendin-4 as a pyroptotic inhibitor protecting against hyperglycemia-induced cardiomyocyte pyroptosis via the AMPK-TXNIP pathway.